2002
DOI: 10.1161/01.hyp.0000014616.48920.8f
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Backscatter and Serum Marker of Cardiac Fibrosis in Hypertensives

Abstract: Abstract-Elevations in the serum concentration of the carboxy-terminal propeptide of procollagen type I (PIP) Ͼ127 g/L have been found to predict severe myocardial fibrosis in hypertensive patients. This study was designed to assess whether ultrasonic reflectivity, evaluated by a real-time integrated backscatter analysis, was related to the severity of myocardial fibrosis as estimated by serum PIP. Thirty-four subjects were included in the study. Serum PIP was measured by specific radio immunoanalysis. Backsca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 42 publications
0
37
2
1
Order By: Relevance
“…Most patients had mild to moderate LV hypertrophy with LV mass indexes ranging from 96 to 166 g/m 2 (10-90 percentile). Previous studies reported that the IBS-CV of the mid-septum in normo- tensive subjects was 6.5-7.0 dB (13,14), which was higher than the IBS-CV levels (5.08±0.51 dB) in our patients. Thus, it is suggested that myocardial collagen deposition was increased in patients in this study.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Most patients had mild to moderate LV hypertrophy with LV mass indexes ranging from 96 to 166 g/m 2 (10-90 percentile). Previous studies reported that the IBS-CV of the mid-septum in normo- tensive subjects was 6.5-7.0 dB (13,14), which was higher than the IBS-CV levels (5.08±0.51 dB) in our patients. Thus, it is suggested that myocardial collagen deposition was increased in patients in this study.…”
Section: Discussioncontrasting
confidence: 84%
“…Among the tissue characterization parameters, the IBS-CV and the peak diastolic IBS value are commonly used as non-invasive parameters of myocardial fibrosis in hypertensive patients. However, the IBS-CV analysis has higher sensitivity than the peak diastolic IBS analysis (13,14,22). Thus, in the present study, the IBS-CV was used as a measure of myocardial fibrosis.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…At the same time, IBS CV was found to be significantly and inversely related to the percent fibrosis area as assessed by endomyocardial biopsy in patients with dilated cardiomyopathy (17) and to the myocardium/fibrosis ratio in patients with aortic stenosis (18). Furthermore, in patients with EH, a decreased CV of backscatter signal is associated with an increase in serum procollagen type I C-peptide, a specific circulating marker of cardiac collagen content (30). In our study, the modest reduction of IBS CV that was observed in patients with CRF and the more relevant decrease of CV IBS that was observed in patients with ESRD, as well as the significant correlation with indices of systolic function, might reflect a progressive impairment of LV contractile performance, possibly associated with an increase in myocardial collagen content.…”
Section: Discussionmentioning
confidence: 96%
“…Ultrasonic tissue characterization with integrated backscatter (IB) offers a promising method for the assessment of myocardial texture and intrinsic contractile performance [7,8]. Previous studies have investigated ultrasonic tissue characterization in patients with DCM, and have shown that the analysis of IB has the potential to assess the myocardial interstitial fibrosis and intrinsic myocardial contractility in DCM [9,10].…”
Section: Introductionmentioning
confidence: 99%